ON CHARACTERISTIC SUBGRAPH OF A GRAPH - Yarahmadi, Zahra; Ashrafi, Ali Reza (Italian Journal of Pure and Applied Mathematics, 2014)
A subgraph H of a graph G is called characteristic if <code class="KDcb0c" dir="ltr" data-sfc-root="ep" data-complete="true" data-copy-service-computed-style="font-family: monospace; font-size: 14px; font-weight: 400; margin: 0px; text-decoration: none; border-bottom: 1px solid rgb(243, 245, 246);">φ(H) = H, for each automorphism <code class="KDcb0c" dir="ltr" data-sfc-root="ep" data-complete="true" data-copy-service-computed-style="font-family: monospace; font-size: 14px; font-weight: 400; margin: 0px; text-decoration: none; border-bottom: 1px solid rgb(243, 245, 246);">φ ∈ Aut(G). In this paper, the main properties of this new concept in algebraic graph theory are presented.